Institutional Ownership Differences and International Diversification: The Effects of Boards of Directors and Technological Opportunity - Tihanyi, László; Johnson, Richard A.; Hoskisson, Robert E.; Hitt, Michael A. (Academy of Management Journal, 2003)
We examined the roles of institutional investors, boards of directors, and technological opportunity in relation to international diversification. Our research contributes to both agency and foreign direct investment theories. In data on 197 large U.S. firms, we found significant relationships between institutional ownership and international diversification. International diversification was favored by (1) professional investment funds along with outside board members and (2) pension funds along with inside board members. Also, pension funds' long-term orientation facilitated internationalization in industries with high technological opportunities. The results suggest that different institutional owners have different stakes in firms' international strategies, and the effects of boards of directors and technological opportunity accentuate these differences.